The multifactorial aetiology of fracture nonunion and the importance of searching for latent infection. Issue 10 (October 2016) - Mills, L.; Tsang, J.; Hopper, G.; Keenan, G.; Simpson, A. H. R. W.
Abstract : Objectives: A successful outcome following treatment of nonunion requires the correct identification of all of the underlying cause(s) and addressing them appropriately. The aim of this study was to assess the distribution and frequency of causative factors in a consecutive cohort of nonunion patients in order to optimise the management strategy for individual patients presenting with nonunion. Methods: Causes of the nonunion were divided into four categories: mechanical; infection; dead bone with a gap; and host. Prospective and retrospective data of 100 consecutive patients who had undergone surgery for long bone fracture nonunion were analysed. Results: A total of 31% of patients had a single attributable cause, 55% had two causes, 14% had three causes and 1% had all four. Of those (31%) with only a single attributable cause, half were due to a mechanical factor and a quarter had dead bone with a gap. Mechanical causation was found in 59% of all patients, dead bone and a gap was present in 47%, host factors in 43% and infection was a causative factor in 38% of patients. In all, three of 58 patients (5%) thought to be aseptic and two of nine (22%) suspected of possible infection were found to be infected. A total of 100% of previously treated patients no longer considered to have ongoing infection, had multiple positive microbiology results. Conclusion: Two thirds of patients had multiple contributing factors for their nonunion and 5% had entirely unexpected infection. This study highlights the importance of identifying all of the aetiological factors and routinely testing tissue for infection in treating nonunion. It raises key points regarding the inadequacy of a purely radiographic nonunion classification system and the variety of different definitions for atrophic nonunion in the current mainstream classifications used for nonunion. Cite this article: L. Mills, J. Tsang, G. Hopper, G. Keenan, A. H. R. W. Simpson. The multifactorial aetiology of fracture nonunion and the importance of searching for latent infection. Bone Joint Res 2016;5:512–519. DOI: 10.1302/2046-3758.510.BJR-2016-0138.